Comparison between calcium carbonate and β-tricalcium phosphate as additives of 3D printed scaffolds with polylactic acid matrix - Donate, R. (2020)
In this study, polylactic acid (PLA)‐based composite scaffolds with calcium carbonate (CaCO3) and beta‐tricalcium phosphate (β‐TCP) were obtained by 3D printing. These structures were evaluated as potential 3D structures for bone tissue regeneration. Morphological, mechanical, and biological tests were carried out in order to compare the effect of each additive (added in a concentration of 5% w/w) and the combination of both (2.5% w/w of each one), on the PLA matrix. The scaffolds manufactured had a mean pore size between 400–425 μm and a porosity value in the range of 50–60%. According to the results, both additives promoted an increase of the porosity, hydrophilicity, and surface roughness of the scaffolds, leading to a significant improvement of the metabolic activity of human osteoblastic osteosarcoma cells. The best results in terms of cell attachment after 7 days were obtained for the samples containing CaCO3 and β‐TCP particles due to the synergistic effect of both additives, which results in an increase in osteoconductivity and in a microporosity that favours cell adhesion. These scaffolds (PLA:CaCO3:β‐TCP 95:2.5:2.5) have suitable properties to be further evaluated for bone tissue engineering applications.